Carbon nanotube–amorphous silicon hybrid solar cell with improved conversion efficiency. (23rd March 2016) - Funde, Adinath M; Nasibulin, Albert G; Syed, Hashmi Gufran; Anisimov, Anton S; Tsapenko, Alexey; Lund, Peter; Santos, J D; Torres, I; Gandía, J J; Cárabe, J; Rozenberg, A D; Levitsky, Igor A
Abstract: We report a hybrid solar cell based on single walled carbon nanotubes (SWNTs) interfaced with amorphous silicon (a-Si). The high quality carbon nanotube network was dry transferred onto intrinsic a-Si forming Schottky junction for metallic SWNT bundles and heterojunctions for semiconducting SWNT bundles. The nanotube chemical doping and a-Si surface treatment minimized the hysteresis effect in current–voltage characteristics allowing an increase in the conversion efficiency to 1.5% under an air mass 1.5 solar spectrum simulator. We demonstrated that the thin SWNT film is able to replace a simultaneously p-doped a-Si layer and transparent conductive electrode in conventional amorphous silicon thin film photovoltaics.